2008
DOI: 10.3174/ajnr.a1133
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Encephalomyeloradiculitis: Report of 2 Cases with Neuroimaging and 1 Case with Autopsy Findings

Abstract: SUMMARY:Chikungunya, an alphavirus presenting with fever, rash, and polyarthritis, is derived from the Makonde word that means "that which bends up," in reference to the crippling manifestations of the disease. Most often it is a self-limiting febrile illness. Neurologic complications of Chikungunya infection have been reported. We are reporting the clinical and neuroimaging data in 2 patients with Chikungunya encephalomyeloradiculitis and brain autopsy findings in 1 patient. Chikungunya virus was first isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 6 publications
(6 reference statements)
4
89
1
4
Order By: Relevance
“…Such findings were rather unique and were also reported in patients with CHIK in India. 21,22 A pathologic correlation with autopsy specimens suggested that these findings were caused by the subcortical demyelination process. 22 Although such findings have been described in Nipah virus encephalopathy, they were quite distinct from Japanese encephalitis or herpes virus encephalitis, which affect only the gray matter, 23 are patchy lesions, and are usually involve the thalamus.…”
Section: 18mentioning
confidence: 99%
See 3 more Smart Citations
“…Such findings were rather unique and were also reported in patients with CHIK in India. 21,22 A pathologic correlation with autopsy specimens suggested that these findings were caused by the subcortical demyelination process. 22 Although such findings have been described in Nipah virus encephalopathy, they were quite distinct from Japanese encephalitis or herpes virus encephalitis, which affect only the gray matter, 23 are patchy lesions, and are usually involve the thalamus.…”
Section: 18mentioning
confidence: 99%
“…21,22 A pathologic correlation with autopsy specimens suggested that these findings were caused by the subcortical demyelination process. 22 Although such findings have been described in Nipah virus encephalopathy, they were quite distinct from Japanese encephalitis or herpes virus encephalitis, which affect only the gray matter, 23 are patchy lesions, and are usually involve the thalamus. 24 Patient 3 had acute progressive quadriparesis and myeloneuropathy confirmed by MRI and electromyography, which showed acute sensorimotor peripheral neuropathy typical for demyelinating disease.…”
Section: 18mentioning
confidence: 99%
See 2 more Smart Citations
“…CHIKV is a re-emerging alphavirus that can cause severe and fatal disease with CNS involvement of both adults and neonates [11][12][13][14]. Prior to its re-emergence in the Indian Ocean in 2004 and ensuing worldwide spread, CHIKV infections rarely involved the CNS.…”
Section: Epidemiology Of Encephalitic Arbovirusesmentioning
confidence: 99%